AVALIAÇÃO DE DESEMPENHO POR MEIO DA VERIFICAÇÃO PROJETUAL EM EDIFÍCIOS VERTICAIS DE HIS - Martins, Natália Costa; Oliveira, Fabiana Lopes de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Allegations regarding housing have focused on several aspects, one of which is the user's perception of the quality of social housing construction systems and processes. The large-scale production of these affordable homes reflects the lack of design quality of the buildings of Social Interest Housing (HIS) in Brazil. However, this scenario has been changing after publication of the Brazilian technical standard NBR 15575:2013 Residential Housing Performance , since it is aimed not only on ensuring the components of these buildings during their service life but also on the technology of the buildings overall construction process, performance assessment has become an important practice. This research involves three case studies of buildings built by the program My House, My Life (Minha Casa, Minha Vida, in Portuguese) in the city of Sorocaba, state of São Paulo (SP), between 2009 and 2015, analyzing their compliance in the projects with the performance criteria for such residential buildings. The aim is to create design and construction parameters for future social housing in the city of Sorocaba, SP, with performance as a factor of quality, well-being and health for the people that live in them.